ANALISIS KINERJA EKONOMI USAHA PENGOLAHAN IKAN BAUNG (Hemibagrus nemurus) ASAP DI KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA - Ferry Bima Prasetya; Gusti Haqiqiansyah; Eko Sugiharto (2339-1324, 2024)
The smoked fish processing business is an effort to increase the added value of the product. The purpose of this study is to find out the cost, receipts, income, break-even point and the ratio of receipts and costs. This research was carried out from January to June 2022. The sample taken was 4 respondents. The data analysis method used is the analysis of income and the ratio of receipts and costs. The results showed that the average total cost of the baung fish processing business was IDR 11,104,250 and the average receipt from the baung fish processing business was IDR 13,605,000 / month and the income from the smoked baung fish processing business in Kota Bangun District averaged IDR 2,500,750 / month. The ratio value of the smoked baung fish processing business in Kota Bangun District is 1.2. Keywords: Economic Performance, Smoked Baung Fish, Kota Bangun District